Recent Progress in Organic–Inorganic Composite Solid Electrolytes for All‐Solid‐State Lithium Batteries. Issue 8 (19th November 2019) - Zhang, Dechao; Xu, Xijun; Qin, Yanlin; Ji, Shaomin; Huo, Yanping; Wang, Zhuosen; Liu, Zhengbo; Shen, Jiadong; Liu, Jun
Abstract: Conventional lithium‐ion batteries, with flammable organic liquid electrolytes, have serious safety problems, which greatly limit their application. All‐solid‐state batteries (ASSBs) have received extensive attention from large‐scale energy‐storage fields, such as electric vehicles (EVs) and intelligent power grids, due to their benefits in safety, energy density, and thermostability. As the key component of ASSBs, solid electrolytes determine the properties of ASSBs. In past decades, various kinds of solid electrolytes, such as polymers and inorganic electrolytes, have been explored. Among these candidates, organic–inorganic composite solid electrolytes (CSEs) that integrate the advantages of these two different electrolytes have been regarded as promising electrolytes for high‐performance ASSBs, and extensive studies have been carried out. Herein, recent progress in organic–inorganic CSEs is summarized in terms of the inorganic component, electrochemical performance, effects of the inorganic ceramic nanostructure, and ionic conducting mechanism. Finally, the main challenges and perspectives of organic–inorganic CSEs are highlighted for future development. Abstract : Best of both worlds : Organic–inorganic composite solid electrolytes (CSEs) integrate the merits of organic polymers and inorganic ceramics. These CSEs, with superior electrochemical and mechanical properties, such as high ionic conductivity, high flexibility, and good thermostability, are considered to be promising electrolytes for next‐generation high energy density batteries.